Effects of compressive stress on the dielectric properties of PIN-PT ceramics - N. Triamnak (2018)
Lead indium niobate, Pb(In1/2Nb1/2)O3 (PIN), is an interesting ferroelectric due to a transition from a disordered to an ordered state by long-time thermal annealing. However, the temperature related to the maximum dielectric constant (Tmax) of PIN in relaxor phase is low (at 1 kHz, Tmax = 66 °C). In this study, lead titanate PbTiO3 (PT) was added to PIN with compositions (1 - x)PIN-xPT (for x = 0.1-0.5) to increase their Tmax. The influence of stress on dielectric properties of (1 - x)PIN-PT ceramics was then investigated. The dielectric properties were measured under various uniaxial compressive stresses up to 400 MPa. The results showed the reduction of dielectric constant in 0.9PIN-0.1PT with superimposed compression load. For other compositions, dielectric constants first increased with compressive stress, then decreased when the stress was further increased up to 400 MPa. The loss tangent of all composition was found to decrease with increasing compressive stress. © 2008.